The way to socialism - Bernd Breuer (Intereconomics, 1971)
The election of Salvador Allende, the representative of the Marxist parties, as Chile's new president on October 24, 1970, meant the end of an important phase in the country's development. We take the opportunity of this event to reflect upon the last five years of Christian-Democrat rule under the Frei government as well as on the achievements during this period and the problems still left unsolved.
Keywords: 330; Chile